2016
DOI: 10.1037/emo0000123
|View full text |Cite
|
Sign up to set email alerts
|

Perceptions of variability in facial emotion influence beliefs about the stability of psychological characteristics.

Abstract: Beliefs about the malleability versus stability of traits (incremental vs. entity lay theories) have a profound impact on social cognition and self-regulation, shaping phenomena that range from the fundamental attribution error and group-based stereotyping to academic motivation and achievement. Less is known about the causes than the effects of these lay theories, and in the current work the authors examine the perception of facial emotion as a causal influence on lay theories. Specifically, they hypothesized… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
6
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 40 publications
2
6
0
Order By: Relevance
“…However, in the pilot study we measured participant beliefs after completing the rating task. Taken together, our findings might suggest that exposure to variable images amplify beliefs about personality, as Weisbuch et al (2016) proposed, more than these beliefs guide trait impressions. We also found that these associations were apparent in the ungrouped conditions; it is difficult to explain how beliefs about personality would be predictive of rating variability when participants are not aware of which images belong to a given identity.…”
Section: Beliefs About Traits and Variability In Trait Judgementssupporting
confidence: 67%
See 1 more Smart Citation
“…However, in the pilot study we measured participant beliefs after completing the rating task. Taken together, our findings might suggest that exposure to variable images amplify beliefs about personality, as Weisbuch et al (2016) proposed, more than these beliefs guide trait impressions. We also found that these associations were apparent in the ungrouped conditions; it is difficult to explain how beliefs about personality would be predictive of rating variability when participants are not aware of which images belong to a given identity.…”
Section: Beliefs About Traits and Variability In Trait Judgementssupporting
confidence: 67%
“…However, some research has demonstrated a relationship between these beliefs and social perception. Weisbuch et al (2016) investigated whether exposure to within-person variability in emotional expression would influence implicit beliefs about the stability of personality (Chiu et al, 1997).…”
Section: Beliefs About Personality and Social Perceptionsmentioning
confidence: 99%
“…Scholars have also begun to explore how observers make trait inferences from changing emotional expressions. Some research indicates that variable facial emotional expressions inform inferences of dynamic (rather than stable) traits (Weisbuch et al 2016), whereas other work suggests that more recent facial expressions overrule earlier ones in shaping trait inferences (Fang et al 2018).…”
Section: Inferential Processes Elicited By Emotional Expressionsmentioning
confidence: 99%
“…During the test, the mean correct rate and reaction time from presentation of the pictures to pushing of the buttons were recorded. The test-retest reliability for emotional face identification is 0.93 [ 29 , 30 , 31 ] ( Figure 1 ). Faster reaction times and more correct responses in the Emotional Perception test represent better emotional perception [ 29 , 30 , 31 ].…”
Section: Methodsmentioning
confidence: 99%